Analisis Pendapatan Petani Pala Di Kampung Brongkendik Distrik Fakfak Tengah Kabupaten Fakfak - Lakupais, Nonce Oktavina; Wanma, Johanis R. (Jurnal Manajemen dan Bisnis, ISSN : 2615 - 0425 (Print), e-ISSN : 2622 - 7142 (Online))
The study aims 1) To analyze the income Of nutmeg farmer per one harvest seasons at Brongkendik Village in the middle of Fakfak Regency.2) To determine factors that affect the income level of nutmeg growers at Brongkendik village in the middle of Fakfak regency.The study used income analysis arithmetic, income statement, R/C Ratio and BEP. Based on the calculation result, it can be concluded that the average earning farmer in one harvest season is Rp.9,503,000,- maximum Rp.39,950,000,- with R/C income of nutmeg growers is at least 6.43 maximum of 13.01 which means that every Rp.1.00 used in one harvest season will produce minimum revenue of Rp.6,43. The acquisition value of R/C is >1, or with another word that is advantageous for the farmer of Nutmeg at Brongkendik village in the middle of Fakfak regency. With minimum value of BEP is Rp.103,643 maximum Rp.192,558 so farmers do not suffer losses and profits.